THE ROLE OF SELF-EFFICACY MEDIATION IN INCREASING ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF CLASS C PRIVATE HOSPITAL AT BEKASI - Gracesia kwannandar; Rokiah Kusumapradja; Nofierni Nofierni (Jurnal Health Sains, 2023)
Organizational citizenship behavior is an important thing that must be considered by hospitals because it can affect overall organizational performance. The low voluntary behavior of helping each other among colleagues and the lack of teamwork and support among others can affect all processes in the workplace, both in terms of work productivity and organizational profitability. The purpose of this study was to analyze the effect of diversity in the workplace and organizational culture on organizational citizenship behavior with self-efficacy as a mediator. The role of self-efficacy can help overcome the obstacles associated with low organizational citizenship behavior, including low organizational culture and differences arising from diversity. This research is explanatory with a quantitative approach in the form of using causal hypotheses with a sample of 90 health workers. This study uses the SEM-PLS (Structural Equation Modeling-Partial Least Squares) method to examine the model and the relationship between variables. In this study, self-efficacy was found to mediate the relationship between organizational culture and diversity in the workplace and organizational citizenship behavior. Organizational culture has a positive and significant effect on organizational citizenship behavior, but diversity in the workplace does not have a significant effect on organizational citizenship behavior. Diversity in the workplace and organizational culture have a positive and significant influence on self-efficacy. The implications of this research theoretically prove the effect of research variables, and managerially, it can be used as an effective strategy to improve organizational citizenship behavior and create a good and productive work environment for health workers.